2020
DOI: 10.1002/ange.201912051
|View full text |Cite
|
Sign up to set email alerts
|

Guanine‐Stabilized Formamidinium Lead Iodide Perovskites

Abstract: Formamidinium (FA) lead iodide perovskite materials feature promising photovoltaic performances and superior thermal stabilities. However, conversion of the perovskite α‐FAPbI3 phase to the thermodynamically stable yet photovoltaically inactive δ‐FAPbI3 phase compromises the photovoltaic performance. A strategy is presented to address this challenge by using low‐dimensional hybrid perovskite materials comprising guaninium (G) organic spacer layers that act as stabilizers of the three‐dimensional α‐FAPbI3 phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…[12,23] This limitation stimulated the appearance of another approach that involves forming 2D/3D perovskite composites of 3D perovskite compositions with 2D overlayers, which show good photovoltaic performance with improvement in their opera tional stability. [24][25][26][27][28][29] In this regard, 2phenylethylammonium (PEA) has been particularly effective (Figure 2a). [30][31][32][33] It has been shown that phenylalkylammonium analogues, e.g., ben zylamine and aniline, can impart the formamidinium (FA) lead iodide film surface with improved electronic properties and moisture resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[12,23] This limitation stimulated the appearance of another approach that involves forming 2D/3D perovskite composites of 3D perovskite compositions with 2D overlayers, which show good photovoltaic performance with improvement in their opera tional stability. [24][25][26][27][28][29] In this regard, 2phenylethylammonium (PEA) has been particularly effective (Figure 2a). [30][31][32][33] It has been shown that phenylalkylammonium analogues, e.g., ben zylamine and aniline, can impart the formamidinium (FA) lead iodide film surface with improved electronic properties and moisture resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, many efforts have focused on stabilizing the 𝛼-phase to achieve high-quality and phase-pure film. [11,12] Some researchers attempted to make compositional engineering by mixing with small radius cations, such as Cs + , Rb + , and MA + , to reduce lattice strain. [13][14][15] Among them, MAPbBr 3 with both smaller cations and anions is commonly used in the FAPbI 3 preparation to maximize 𝛼-phase stability.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Because of narrower light absorption range and high excitonic binding energy, LD perovskites are not ideal materials to apply directly on photovoltaic devices (PV). [18] Thus, it has been suggested to combine 2D and 3D perovskites to generate a 2D/3D heterostructure via additive engineering, [19,20] interfacial engineering, [21,22] or directly establishing a quasi-2D perovskite. [23,24] These strategies are particularly efficient in solving stability issues of 3D perovskite.…”
Section: Introductionmentioning
confidence: 99%